Sharia Firm Value: The Role of Enterprise Risk Management Disclosure, Intellectual Capital Disclosure, and Intellectual Capital - Pratama, Bima Cinintya; Sasongko, Karin Maharani; Innayah, Maulida Nurul (IAIN Surakarta, 2020)
This present study aims to determine the effect of enterprise risk management disclosure, intellectual capital disclosure, and intellectual capital towards firm value. The population in this study is sharia commercial banks in Indonesia from 2010 through 2018. This research employs the purposive sampling technique to obtain a sample of 106 companies that met the criteria. Multiple regression analysis using the SPSS program was employed as the data analysis technique. The results of this study revealed that enterprise risk management disclosure has a positive effect on firm value. Moreover, the intellectual capital disclosure variable has negatively related to firm value. The intellectual capital variable, however, does not affect the firm value. The results of this study imply that sharia commercial banks are encouraged to optimize their risk management through the application of enterprise risk management. Moreover, the results further suggest that the sharia banks should also improve their intellectual capital performances to create a competitive advantage for the banks, and therefore it brings higher values for the banks.Â